ESENSI KURIKULUM DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Ramadhan Saleh Lubis (UIN Sumatera Utara Medan, 2017)
Curriculum discussion based on philosophy of Islamic education is a must to do. Because the philosophy of Islamic education is a compass and the foundation for various activities and educational activities to achieve educational goals. Islamic education curriculum is all efforts and educational activities that help learners in growing their personality in accordance with the nature of human creation, which makes it as obedient and faithful servant of God, as well as the bearer of the mandate as the khalifah of Allah who will prosper the earth.The principles of Islamic education curriculum are fundamental foundations that must be adhered to in implementing and developing the curriculum, of course, in the philosophical view of Islamic education, these principles are closely related to the source of Islamic values are the Qur'an and as-Sunnah. There are four principles of Islamic education curriculum : religious principles, principles of philosophy, psychological principles, and social principles.In the perspective of Islamic educational philosophy, the formulation of educational curriculum characteristics is a reflection of Islamic values, which are of course sourced from the Qur'an and as-Sunnah, formed in philosophy and manifested in all practices or activities and educational experiences. Finally Islamic philosophy of education asserts that the scope of Islamic education curriculum should be directed to the activities that cultivate human beings, whether as a servant to God (abd Allah), as well as human beings as khalifah